Generating credible weather data for future climates - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Knowledge about future weather conditions, such as when the rains will fall and for how long, is crucial for farmers’ decision-making. In sub-Saharan Africa, 95% of farmland is rainfed agriculture. Persistent events such as drought and prolonged rainfall can spell disaster, which is why being able to project what the weather will be like is critical. Weather data are also required for global and regional circulation models, the most advanced tools currently available for simulating the response of the global climate system. Global circulation models (GCMs) have become increasingly important for climate change science and provide the basis for most impact studies. While climate models are suitable tools for evaluating risk, they require accurate daily weather data to feed into model development. Particularly in developing countries, the availability and quality of historical weather data is often limited. An online tool is now helping to make weather data freely available worldwide.